2019
DOI: 10.4102/ojvr.v86i1.1671
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis knowledge, attitudes and practices of a South African communal cattle keeper group

Abstract: Brucellosis remains an animal and public health concern in South Africa, given the intensity and widespread distribution of outbreaks in cattle. We conducted a cross-sectional survey among cattle keepers in the Whittlesea community of the Eastern Cape Province of South Africa, which utilises communal grazing. Individual cattle keepers ( N = 227) who attended prearranged meetings in selected villages were interviewed using a structured questionnaire to assess their knowledge, attitude and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 13 publications
6
32
3
Order By: Relevance
“…The situation in KUNAK had a similarity to a study done by Cloete et al (2019) regarding the knowledge of South African cattle keeper group on brucellosis stated that even when the participants (respondents) knew about brucellosis and their government stand on vaccination and controlling it, but they lacked more in-depth knowledge with particular reference to zoonotic implications and disease prevention.…”
Section: Specific Knowledge Of Brucellosis By Categorymentioning
confidence: 72%
“…The situation in KUNAK had a similarity to a study done by Cloete et al (2019) regarding the knowledge of South African cattle keeper group on brucellosis stated that even when the participants (respondents) knew about brucellosis and their government stand on vaccination and controlling it, but they lacked more in-depth knowledge with particular reference to zoonotic implications and disease prevention.…”
Section: Specific Knowledge Of Brucellosis By Categorymentioning
confidence: 72%
“…Studies have revealed that men were more likely to have the disease in comparison to women, suggesting that it was due to the type of work, more contact with livestock, and their products. [ 31 32 ] Contrary to these studies, a study in Saudi Arabia showed that the prevalence of brucellosis was higher in women than in men. [ 33 ]…”
Section: Discussionmentioning
confidence: 98%
“…However, our model assured the significant flow from knowledge via attitudes to practice. The KAP model has been applied in many countries for a wide variety of health and animal health problems ( 32 , 45 ); however, during our FGDs, several farmers in different sectors described that even though they wanted to, they could not tighten biosecurity because farm labor and facilities are limited. We conceptualized that capacity, which is equivalent to self-efficacy in PMT ( 23 ) and PBC in the TPB ( 28 ), can be a prerequisite to high biosecurity performance.…”
Section: Discussionmentioning
confidence: 99%